(untitled) (Homoeopathy for All, 2025)
Background of Schedule M1 First time the Schedule M1 was notified in 1987, G.S.R. 507(E), dated 12-06-1987, w.e.f. 12-06- 1987.; which had a basic requirement for Factory premises, requirement of plant and equipment for manufacture of Homoeopathic Medicines. In 2006, it was again notified, G.S.R. 678(E), dated 31-10-2006, w.e.f. a date on or after two years of its publication, i.e. 31-10-2006; which had a detailed information mainly on general requirements, plant and equipment, facilities, personnel, Quality control division, raw materials, procedures, Laboratory controls, SOPs, Records and Registers, etc. The Government has the responsibility to safeguard the public health on one-side and to see that industry goes into the right direction. Keeping this thing in mind, the Government revises Schedule M1; which deals with the Good Manufacturing Practices.